Ranchers or pastoralists? Farm size, specialisation and production strategy amongst cattle farmers in south-eastern Kazakhstan - Sarah Robinson; Zhanyl Bozayeva; Nozilakhon Mukhamedova; Nodir Djanibekov; Martin Petrick (Pastoralism: Research, Policy and Practice, 2021)
Against the global trend towards sedentary, specialised and feed-intensive cattle farming, we explore current patterns of production in Kazakhstan's traditionally nomadic livestock sector. Experts see considerable potential for output expansion, and the government hopes to promote the sector as an alternative to revenues from hydrocarbons. Which production systems emerge will determine the use of the country's vast pastoral resources, patterns of economic contribution from livestock and future greenhouse gas emissions. We focus on the beef sector, using original survey data and interviews from south-eastern Kazakhstan to compare rural households and farms by production strategy, generated using cluster analysis from data on livestock holdings, fodder provision and grazing. We examine in particular the relationships between farm size and the characteristics identified. We find that, rather than being specialised and intensive, larger farms tend to be highly diversified in terms of stock species, are more mobile and provide fewer supplements per head than smaller farms. Winter pastures appear to be a key resource associated with larger operations. Many large farms provide fodder mainly as low-quality roughage, although a subset with better access to cropland provide higher quality rations and fatten cattle before sale. Medium-sized farms lack either winter pasture bases or cropland for growing supplements, but proximity to markets enables some to compensate through fodder purchases. Inability to access government support, available only to large farms, hampers their expansion. Farmers' professional background, distance from markets and environmental conditions are all associated with the production systems observed. In terms of policy, high transaction costs associated with leaseholds and lack of transferability between farmers impede access to land. Current pasture access mechanisms and institutions almost entirely exclude small farms and households. Changes in these systems, combined with infrastructure development, may bring economic, social and environmental benefits for the livestock sector and rural communities.
Keywords: 330; Kazakhstan; livestock; pasture; fodder; intensification